Electron transfer in DNA duplexes containing 2-methyl-1,4-naphthoquinone - Bergeron, François (Oxford University Press, 2004)
2-Methyl-1,4-naphthoquinone (menadione, MQ) was linked to synthetic oligonucleotides and exposed to near-UV light to generate base radical cations in DNA. This model system of electron transfer induced alkali-labile breaks at GG doublets, similar to anthraquinone and metallointercalators systems. In sharp contrast to other systems, the photolysis of MQ–DNA duplexes gave interstrand cross-links and alkali-labile breaks at bases on the complementary strand opposite the MQ moiety. For sequences with an internal MQ, the formation of cross-links with A and C opposite the MQ moiety was 2- to 3-fold greater than that with G and T. The yield of cross-links was more than 10-fold greater than that of breaks opposite MQ, which in turn was more than 2-fold greater than breaks at GG doublets. The yield of damage at GG doublets greatly increased for a sequence with a terminal MQ. The distribution of base damage was measured by enzymatic digestion and HPLC analysis (dAdo > dThd > dGuo > dCyd). The formation of novel products in MQ–DNA duplexes was attributed to the ability of excited MQ to generate the radical cations of all four DNA bases; thus, this photochemical reaction provides an ideal model system to study the effects of ionizing radiation and one-electron oxidants.